Ispagula powder – an allergen in the work environment - Göransson, Kersin; Michaelson, Gunnar (Scandinavian Journal of Work, Environment & Health, 1979)
Bulk laxatives based on ispagula powder have given no known allergic side effects when administered perorally. Twenty-seven out of 64 workers in a pharmaceutical factory developed rhinitis, conjunctivitis or asthma when engaged in the packing of ispagula husks, an operation which gives rise to dust. The symptoms are accounted for by a type 1 allergy acquired from ispagula husks. This allergy can be demonstrated by intracutaneous and provocation tests. Occupational health measures were taken which reduced the dust content to a minimum; thereafter only one new case of sensitization was recorded during the next 24 months of observation. Five similar cases were reported among nursing staff exposed to the dust of ispagula while administering doses of bulk laxative.
Keywords: allergen; asthma; bulk laxative; conjunctivitis; dust; ispagula; ispagula powder; psyllium seed; rhinitis; type 1 allergy; work environment